The complete mitochondrial genome of the Sideridis albicosta (Lepidoptera: Noctuoidea: Noctuidae) - Shun Yao; Zi-Hui Wang; Xiao-Yue Zhu; Jia-Sheng Hao (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitochondrial genome (mitogenome) of Sideridis albicosta is described in this study. The circular molecule is 15,320 bp in length and contains 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and one AT-rich region. Thirteen PCGs is 11,252 bp in total, encoding 3723 amino acids. All PCGs start with ATN, except for COI gene starting with CGA; 10 of the 13 PCGs use the typical stop codon TAA, whereas COI, COII, and ND4 stop with a single T. The rrnL and rrnS genes are 1377 bp and 783 bp in length, respectively. The 328 bp AT-rich region contains several structures characteristic of the lepidopterans. New phylogenetic analyses upon mitogenomics would provide us further insights on the taxonomy and phylogeny of Noctuoidea.